Optimum Growth in an Aggregative Model of Capital Accumulation - Cass, David (Review of Economic Studies, 1965)
Journal Article Optimum Growth in an Aggregative Model of Capital Accumulation Get access David Cass David Cass Yale University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 32, Issue 3, July 1965, Pages 233–240, https://doi.org/10.2307/2295827 Published: 01 July 1965